Antenatal Breast Milk Expression Survey of Individuals Whose Pregnancy Was Complicated by Diabetes: Exploring Knowledge, Perceptions, Experiences, and Milk Volume Expressed - Mess, Sarah; Palatnik, Anna; Cabacungan, Erwin (American Journal of Perinatology, 2024)
Objective Antenatal breast milk expression (ABE) offers a host of benefits, including reduced formula consumption, support for breastfeeding success, and increased maternal satisfaction. Despite these advantages, experience with ABE differs significantly, often leading to anxiety over perceived inadequate milk supply and eventual breastfeeding cessation. This study comprehensively evaluates the knowledge, attitudes, and real-world experiences of individuals with gestational or pregestational diabetes concerning ABE, with a focus on total milk volume expressed prior to birth.Study Design Utilizing a convenience sampling method, we surveyed individuals with gestational or pregestational diabetes from three health care facilities who were trained in ABE. Knowledge and perceptions were gauged through presurvey statements, while postsurvey statements were employed to measure experiences, both using a 5-point Likert scale. In parallel, a retrospective study assessed both maternal and infant outcomes among the same participant pool. Statistical comparisons between individuals with and without reservations were made using the Wilcoxon signed rank sum, Mann–Whitney, chi-square, and Fisher's exact tests.Results Of the 138 participants, 75% completed both survey segments, and 61% expressed reservations about ABE. Both groups were demographically similar and showed comparable newborn outcomes. However, individuals with reservations experienced heightened pain during ABE, reported lesser lactation support, and were less willing to repeat the process compared to those individuals without reservations. The median total ABE volume was significantly lower by 14 mL among those with reservations (7 vs. 21 mL, p = 0.009). Although both groups demonstrated improved attitudes toward the utility of ABE for individuals with gestational or pregestational diabetes, no significant shift occurred in the perception of ABE difficulty.Conclusion Our results indicate that individuals with gestational or pregestational diabetes who have reservations about ABE face unique challenges and tend to express lower milk volumes. This underlines the need for specialized interventions and ongoing research to address antenatal lactation support and alleviate ABE-related concerns among individuals with gestational or pregestational diabetes.Key Points
Keywords: antenatal breast milk expression; diabetic individuals; milk volumes; colostrum